A prospective association between dietary mushroom intake and the risk of type 2 diabetes: the Korean Genome and Epidemiology Study–Cardiovascular Disease Association Study - Yu-Mi Kim; Hye Won Woo; Min-Ho Shin; Sang Baek Koh; Hyeon Chang Kim; Mi Kyung Kim (Epidemiology and Health)
OBJECTIVES Mushrooms, known for their nutritious and functional components, are considered healthy and medicinal. This study investigated the prospective association between dietary mushroom consumption and the incidence of type 2 diabetes among Korean adults aged ≥40 years. METHODS In total, 16,666 participants who were not taking anti-diabetic medication or insulin and had normal fasting blood glucose (FBG; <126 mg/dL) were included. We used the cumulative average dietary consumption of mushrooms as an exposure metric, calculated from food frequency questionnaires at every follow-up, along with covariates collected during a baseline survey. To estimate incidence rate ratios (IRRs) for type 2 diabetes, a modified Poisson regression model with a robust error estimator was applied. RESULTS In multivariable models, dietary mushroom consumption was inversely associated with type 2 diabetes incidence in both genders (men: IRR, 0.65; 95% confidence interval [CI], 0.47 to 0.90; plinearity=0.043 in the highest quartile (Q4) vs. the lowest quartile (Q1); women: IRR, 0.70; 95% CI, 0.54 to 0.93; plinearity=0.114 in Q4 vs. Q1). The inverse association remained after adjustment for dietary factors instead of dietary quality index, the baseline FBG, and the exclusion of incidence within the first year. Additionally, no significant interaction was found regarding the risk of type 2 diabetes between dietary mushroom consumption and participants’ gender or other factors. CONCLUSIONS Dietary mushroom consumption was inversely linked with the risk of type 2 diabetes incidence in both genders, indicating the beneficial role of mushrooms in preventing the disease.